„Godne Księstwo Litewskie takiego klejnotu” – edycja krytyczna cyklu wierszy dotyczących Pogoni z Pocztu herbów Wacława Potockiego - Piotrowiak, Dariusz (Tematy i Konteksty, 2019)
The paper is a critical edition of Wacław Potocki’s series of poems centered around the Lithuanian coat of arms „Pogonia”. The poems come from a verse book of heraldry: The Coats of Arms of the Nobility of the Polish Crown and the Grand Duchy of Lithuania, published in 1696. The transcription of the works is accompanied by explanations of a multifaceted character.